2010
DOI: 10.1007/s12542-010-0073-x
|View full text |Cite
|
Sign up to set email alerts
|

First description of milk teeth of fossil South American procyonid from the lower Chapadmalalan (Late Miocene–Early Pliocene) of “Farola Monte Hermoso,” Argentina: paleoecological considerations

Abstract: The first record of milk teeth of South American fossil procyonids comes from the Late Miocene-Early

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 13 publications
3
23
0
8
Order By: Relevance
“…Large intraspecific variation has been recognized in extant procyonids (Rodriguez et al 2013) and this could be also the case for the fossil species. In fact, what is treated here as Cyonasua (e.g., Riggs and Patternson 1939;Kraglievich and Reig 1954;Soibelzon 2011) was considered by some authors as different genera (e.g., Baskin, 2004). We followed Patterson and Pascual (1972), Berman (1994), Soibelzon and Prevosti (2007), Soibelzon (2011), Prevosti and Soibelzon (2012), and Prevosti et al (2013) in considering two valid genera for the South American extinct procyonids, although our phylogenetic analysis failed to recognize the monophyly of Chapalmalania (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large intraspecific variation has been recognized in extant procyonids (Rodriguez et al 2013) and this could be also the case for the fossil species. In fact, what is treated here as Cyonasua (e.g., Riggs and Patternson 1939;Kraglievich and Reig 1954;Soibelzon 2011) was considered by some authors as different genera (e.g., Baskin, 2004). We followed Patterson and Pascual (1972), Berman (1994), Soibelzon and Prevosti (2007), Soibelzon (2011), Prevosti and Soibelzon (2012), and Prevosti et al (2013) in considering two valid genera for the South American extinct procyonids, although our phylogenetic analysis failed to recognize the monophyly of Chapalmalania (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 Ma (Woodburne 2010 and references there). Fossil evidence demonstrated that the procyonids predate this episode and are among the first North American immigrants recorded in South America (Marshall et al 1979;Linares 1981;Baskin 1982;Berman 1994;Soibelzon andPrevosti 2007, 2012;Woodburne 2010;Prevosti and Soibelzon 2012). A full closure of the Central American Seaway (or CAS, the oceanic pathway along the tectonic boundary between South America and the Panama Block) occurred by 12-10 Ma, ending the exchange of deep and intermediate waters between the Caribbean and the Pacific (Coates et al 2004;Montes et al 2012a, b;Sepulchre et al 2014).…”
Section: Procyonids and The Great American Biotic Interchangementioning
confidence: 99%
“…Although Cyonasua and Stylocynus coexisted in the late Miocene (Huayquerian SALMA), the earliest species of Cyonasua are also the species with strongest adaptations towards an omnivorous/hypocarnivorous mode of life (based on RGA values; see Prevosti et al, 2013). Soibelzon (2011) also noted that the species of Cyonasua that coexisted with Stylocynus were only about one-fourth of its size; therefore, the two animals were unlikely to be in competition. Only after the extinction of Stylocynus do larger procyonids (Chapalmalania spp.)…”
Section: The Evolution Of South America's Predator Guildmentioning
confidence: 99%
“…and species of procyonids with relatively more pronounced adaptations for carnivory (Cyonasua lutaria and Chapalmalania spp.) appear in the fossil record (Soibelzon, 2011;Prevosti et al, 2013).…”
Section: The Evolution Of South America's Predator Guildmentioning
confidence: 99%
“…Using dental indices, body size, stable isotopes, and taphonomy, Prevosti and Martin (2013) reconstructed the carnivore guild of southern Patagonia in the latest Pleistocene, and discussed potential prey/predator relationships. Soibelzon (2011), based on dental anatomy, suggested that the procyonids of the late Miocene-Pliocene (Cyonasua and Chapalmalania) had a more predatory habit than living ones, and that they became extinct because the immigration of other carnivorans to South America, as was discussed about the extinction of Chapalmalania and the immigration of bears by Kraglievich and de Olazabal (1959). But the dentition of these extinct procyonids lack functional carnassials and the development of large shearing crests typical of more predaceous carnivorans.…”
mentioning
confidence: 99%